Cell-Permeable Succinate Rescues Mitochondrial Respiration in Cellular Models of Amiodarone Toxicity - Alina M. Bețiu (MDPI AG, 2021)
Amiodarone is a potent antiarrhythmic drug and displays substantial liver toxicity in humans. It has previously been demonstrated that amiodarone and its metabolite (desethylamiodarone, DEA) can inhibit mitochondrial function, particularly complexes I (CI) and II (CII) of the electron transport system in various animal tissues and cell types. The present study, performed in human peripheral blood cells, and one liver-derived human cell line, is primarily aimed at assessing the concentration-dependent effects of these drugs on mitochondrial function (respiration and cellular ATP levels). Furthermore, we explore the efficacy of a novel cell-permeable succinate prodrug in alleviating the drug-induced acute mitochondrial dysfunction. Amiodarone and DEA elicit a concentration-dependent impairment of mitochondrial respiration in both intact and permeabilized platelets via the inhibition of both CI- and CII-supported respiration. The inhibitory effect seen in human platelets is also confirmed in mononuclear cells (PBMCs) and HepG2 cells. Additionally, amiodarone elicits a severe concentration-dependent ATP depletion in PBMCs, which cannot be explained solely by mitochondrial inhibition. The succinate prodrug NV118 alleviates the respiratory deficit in platelets and HepG2 cells acutely exposed to amiodarone. In conclusion, amiodarone severely inhibits metabolism in primary human mitochondria, which can be counteracted by increasing mitochondrial function using intracellular delivery of succinate.